Accountability and culture of school principals and teachers an eight-country comparative study - Rozenblaṭ, Zehavah; Wubbels, Th. (London : Routledge, 2021)
Accountability and Culture of SchoolTeachers andPrincipals studies the degree to which teachers and principals in eight countries view themselves as taking responsibility, working by clear standards, reporting transparently, and accepting feedback at work. The book focuses on cultural values that explain variation in accountability levels of school educators, drawing ondata from Canada, China, Hungary, Israel, the Netherlands,Spain, South Africa,and Zimbabwe. It addresses the question of whether cultural values, specifically collectivism and individualism, are related to teachers' and principals' external and internal accountability dispositions. It also explores the intriguing role of organizational support and key school personnel in school reforms across the world, providing a new way to understand school accountability. The book will be of great interest for academics, post-graduate students, and scholars in the field of education policy and international and comparative studies in education.
OCLC-licensed vendor bibliographic record.
Keywords: School management and organization; EDUCATION / General